Natural Elements and Their Metaphors in the Poetry of Ingeborg Bachmann - Özge Aslan; Habib Tekin (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
Ingeborg Bachmann was an outstanding Austrian author and poet of the 20th century who exerted a lasting influence on literature through her profound and introspective exploration of the human condition in the post-war era. Characterized by intellectual depth and a nuanced understanding of complex interpersonal relationships, her works have positioned her as a significant figure in contemporary literature. One captivating aspect of Bachmann’s poetry is her skillful use of nature metaphors, particularly the symbolic representation of fire, water, air, and earth. These natural elements serve as complex metaphors, artfully capturing deep emotional states, the human condition, and the individual’s connection to the natural world. Through these metaphysical connections, Bachmann created a poetic world in which readers can gain valuable insights and seek meaning and identity through the interpretation of nature. The symbols of fire, water, air, and earth convey intensely emotional experiences and existential questions, often evoking memories of wartime and the complex relationship between humanity and the environment. Consequently, this study provides a profound understanding of Bachmann’s poetry and her ongoing quest for connection to the world. It illuminates the inner world of Bachmann’s literary identity, which through her powerful language marked by memories of war, continues to captivate contemporary readers. Bachmann’s work thus becomes an important window offering insight into human existence and its interweaving with nature.